Spring fresh enterprise: Blossom hydration / Farhah Nadhirah Md Nordin... [et al.] - Md Nordin, Farhah Nadhirah; Mohd Salihin, Ilia Izzatie; Omar, Khairunnisa; Suhaimi, Nur Aziela; Wahab, Nur Farahin (2018)
Spring Fresh Enterprise is a home for customers to find a product that able to keep their plant stay fresh and healthy.